2023
DOI: 10.2176/jns-nmc.2022-0271
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impacts of Stereotactic Electroencephalography on Epilepsy Surgery and Associated Issues in the Current Situation in Japan

Abstract: Stereotactic electroencephalography (SEEG) is receiving increasing attention as a safe and effective technique in the invasive evaluation for epileptogenic zone (EZ) detection. The main clinical question is whether the use of SEEG truly improves outcomes. Herein, we compared outcomes in our patients after three types of intracranial EEG (iEEG): SEEG, the subdural electrode (SDE), and a combined method using depth and strip electrodes. We present here our preliminary results from two demonstrative cases. Severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Since recently, implantation of SEEG electrodes with the utilization of various robotic systems has been routinely employed for both adult and pediatric patients in neurosurgical centers globally. 10 - 16 ) To evaluate the effectiveness and safety of the ROSA Ⓡ device concerning accuracy of depth electrode placement, operative time, perioperative complication rates, and seizure outcomes, the presented systematic review and meta-analysis has been specifically directed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since recently, implantation of SEEG electrodes with the utilization of various robotic systems has been routinely employed for both adult and pediatric patients in neurosurgical centers globally. 10 - 16 ) To evaluate the effectiveness and safety of the ROSA Ⓡ device concerning accuracy of depth electrode placement, operative time, perioperative complication rates, and seizure outcomes, the presented systematic review and meta-analysis has been specifically directed.…”
Section: Discussionmentioning
confidence: 99%
“…The use of robotic systems is believed to enhance the precision and accuracy of SEEG electrode implantation. 10 - 16 , 39 ) Indeed, once the trajectory for implantation has been set, the rigidity of the robotic arm reduces involuntary movement, which decreases human error. In their meta-regression analysis, Philipp et al 40 ) demonstrated that robot-assisted stereotactic procedures lessen target error.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of uncertainty about lateralization, judgments about lateralization, irritative zone, and seizure onset zone can be made by inserting intracranial electrodes on both sides [ 14 ]. However, the fact that 20 % of patients do not undergo epilepsy surgery, including focal resection, following intracranial electrode placement and instead have the electrodes removed [ 15 , 16 ], along with the risks of intracranial electrodes [ [17] , [18] , [19] , [20] ], makes invasive studies more difficult to perform compared to non-invasive tests due to the invasiveness. Recently, less-invasive SEEG has been becoming mainstream [ 21 ], but some risk of complications remains [ 22 ].…”
Section: Introductionmentioning
confidence: 99%